Faith Based Organisations Strategies and the welfare of street children in Lango sub-region: Evidence from Lira City, Uganda - Ojok, Fred Ojok; Obici , Gilbert Obici; Mwesigwa, David Mwesigwa (International Journal of Culture and Religious Studies, 2022)
Purpose: The study aimed to examine the relationship between Faith Based Organisations Strategies (FBOS) and Welfare of Street Children (WSC) in Lira City, specifically focusing on the effect of FBOS in terms of preventive strategies, rehabilitation strategies, outreach strategies and collaboration strategies on the WSC. Methodology: The study adopted a descriptive study design, which employed a mixed method approach of both quantitative and qualitative methods. The study population consisted of 219 which included district and sub-county officials, Simple random sampling technique and purposive sampling, was used to select a sample size of 196 participants. The researcher used self-administered questionnaires to collect quantitative data, interview guide and focus group discussion guide to collect qualitative data. Descriptive statistics (mean, and standard deviation), and inferential statistics (correlation and regression) were used to analyse numerical data. Content analysis was used to analyse qualitative data from interviews to supplement quantitative data. Findings: The results revealed a statistically significant positive relationship between FBOS and the WSC. The study also revealed that preventive Strategy had a significant effect on the WSC (Î²=0.061, P<0.01), rehabilitation (Î²=0.625, P<0.01), outreach strategy (Î²=0.096, P<0.01) and Collaborative strategy (Î²=0.086, P<0.01). Conclusion: Based on the findings of this study, it was concluded that FBOS have a significant effect on the WSC in Lira City, northern Uganda. Unique contribution to policy and/or practice: This study contributes an original and empirical-evidence of the relationship between FBOS and the WSC in Uganda. That is why the quest for improved WSC in Lira City calls for concerted engagement among both urban government actors and other non-state actors to mobilize local communities to embrace the FBOS so as to guarantee the WSC in Uganda.